Andragogy approach in conducting forensic crime scene investigation: a summary of teaching practice - Hanis Zainal Abidin NurWaliyuddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Like student-centred learning, andragogy is concerned with adult learning through selfdirected learning, active participation, and collaborative problem-solving. While andragogy has been extensively recognised as a viable method for adult learning, its application presents several obstacles in higher-level education institutions. This article aims to demonstrate how to design and implement this andragogical strategy, particularly in Forensic Science programs. Specifically, this article discusses an andragogical approach to conducting a crime scene investigation as a course assignment. This activity starting with strategizing the teaching plan with students, setting up the crime scene, crime scene reconstruction, presentation of the investigation results, peer evaluation, and getting the student feedback. This activity is often used in Forensic Science programmes to provide students with hands-on experience in processing a crime scene, collecting evidence, and analysing evidence. Typically, instructors prepare crime scenes for students to investigate. Instead of providing a pre-constructed crime scene, students are given the opportunity to create and produce their own crime scenes. This indirectly demands dedication, group cooperation, and wisdom in applying all their knowledge and experience in Forensic Science. This activity provides space for creative thinking among students, especially in creating crime scenes, evaluating evidence materials, and reconstructing crime incidents using the obtained evidence. This article also highlights the need for obtaining student feedback, as well as the knowledge generated, and challenges faced by educators in applying andragogy in learning activities.